The scars of war : Tokyo during World War II : writings of Takeyama Michio - Takeyama, Michio, 1903-1984 (Asian voices (Rowman and Littlefield, Inc.), 2007)
Takeyama Michio, the author of Harp of Burma, was thirty-seven in 1941, the year of the Japanese attack on Pearl Harbor. Husband, father of children born during the war, and teacher at Japan's elite school of higher education in Tokyo, he experienced the war on its home front. This intimate account of the "scars of war," including personal anecdotes from Takeyama's students and family, is one of very few histories from this unique vantage point. Beautifully translated by Richard H. Minear, these honest and moving essays are a fresh look at the history of Japan during the Asia-Pacific Wa